2006
DOI: 10.1139/x06-193
|View full text |Cite
|
Sign up to set email alerts
|

Immediate tree uprooting after retention-felling in a coniferous boreal forest in Fennoscandia

Abstract: We studied the immediate effects of retention-felling on the occurrence of tree uprooting in two different types of boreal spruce forest in Finland to determine whether susceptibility to uprooting is dependent on the biotope. During the first post-treatment year, 7.1% of the trees in the paludified forest type and 1.8% in the upland forest type were uprooted. During the 2 following post-treatment years, uprooting percentages increased considerably (39.3% in the paludified type and 11.5% in the upland type in y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 20 publications
3
25
0
Order By: Relevance
“…This is consistent with all other studies of windthrow following variable retention harvesting (Bebber et al, 2005;Hautala and Vanha-Majamaa, 2006;Steventon, 2011). It thus seems clear that retention cuts increase the risk of windthrow compared to stands situated within an intact forest matrix.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is consistent with all other studies of windthrow following variable retention harvesting (Bebber et al, 2005;Hautala and Vanha-Majamaa, 2006;Steventon, 2011). It thus seems clear that retention cuts increase the risk of windthrow compared to stands situated within an intact forest matrix.…”
Section: Discussionsupporting
confidence: 92%
“…Green tree retention can lead to higher levels of windthrow compared to untouched forests (Bebber et al, 2005;Bladon et al, 2008;Busby et al, 2006;Hautala and Vanha-Majamaa, 2006;Scott and Mitchell, 2005). While gradual tree mortality can provide a desired input of dead wood over the medium term, high levels of mortality in the years immediately following cutting may impact species that depend on standing live trees and compromise the longer term recruitment of dead wood (Thorpe and Thomas, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The smaller the patches (the range was 1/16 to 1 ha), the higher the recorded mortality. Hautala et al (2006) monitored tree dynamics on spruce-dominated patches in southern Finland. In their study area, the size of the retention patches affected tree uprooting only slightly.…”
Section: Retention Patchesmentioning
confidence: 99%
“…Our models on the dead-wood dynamics in the GTR patches may miss some important aspects. For example, it has recently been shown that the amount of CWD may be higher in GTR patches than in comparable mature forests, probably because windstorms increase dead-wood formation in edge-prone GTR patches (Hautala and Vanha-Majamaa 2006;Jönsson et al 2007). Thus, GTR may promote the distribution of key forest attributes in a landscape.…”
Section: Discussionmentioning
confidence: 99%